Key success factors behind electronic medical record adoption in Thailand. Issue 6 (19th September 2016) - Narattharaksa, Kanida; Speece, Mark; Newton, Charles; Bulyalert, Damrongsak
Abstract : Purpose: The purpose of this paper is to investigate the elements that health care personnel in Thailand believe are necessary for successful adoption of electronic medical record (EMR) systems. Design/methodology/approach: Initial qualitative in-depth interviews with physicians to adapt key elements from the literature to the Thai context. The 12 elements identified included things related to managing the implementation and to IT expertise. The nationwide survey was supported by the Ministry of Public Health and returned 1, 069 usable questionnaires (response rate 42 percent) from a range of medical personnel. Findings: The key elements clearly separated into a managerial dimension and an IT dimension. All were considered fairly important, but managerial expertise was more critical. In particular, there should be clear EMR project goals and scope, adequate budget allocation, clinical staff must be involved in implementation, and the IT should facilitate good electronic communication. Research limitations/implications: Thailand is representative of middle-income developing countries, but there is no guarantee findings can be generalized. National policies differ, as do economic structures of health care industries. The focus is on management at the organizational level, but future research must also examine macro-level issues, as well as gain more depth into thinking of individual health care personnel. Practical implications: Technical issues of EMR implementation are certainly important. However, it is clear actual adoption and use of the system also depends very heavily on managerial issues. Originality/value: Most research on EMR implementation has been in developed countries, and has often focussed more on technical issues rather than examining managerial issues closely. Health IT is also critical in developing economies, and management of health IT implementation must be well understood.